Extension programme of the Bambui Dairy Project - Maximuangu, J.C.; Chaleux, L. (1978)
The extension programme of the Bambui Dairy Project is described. Detailed information on responsibilities of the different organisations concerned provided. The advantages and economic feasibility of dairy farming with Red and White Fulani, Red Bororo, Holstein, Friesian and Jersey breeds are discussed in relation to their performance, genetic improvement, milk yield, projected development and training.